FAKTOR FAKTOR YANG MEMPENGARUHI INDEKS PEMBERDAYAAN GENDER DI PROVINSI ACEH - Riska Hafifa; Dena Resvi Nabila; Nurlaila Hanum; Asnidar Asnidar; Puti Andiny; Safuridar Safuridar (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the factors that influence the Gender Empowerment Index (GEI) in Aceh Province from 2010 to 2024. The variables examined include Women as Professional Workers, Women’s Income Contribution, and Women’s Involvement in Parliament. Using secondary data from Statistics Indonesia (BPS), this research applies a quantitative approach with multiple linear regression analysis using Eviews 10. The results show that women as professional workers have a positive but insignificant effect on the GEI. Meanwhile, women’s income contribution and women’s involvement in parliament both have positive and significant effects on the GEI in Aceh Province. The F-test results indicate that all independent variables simultaneously have a significant effect on the GEI. The coefficient of determination (R²) of 0.9966 indicates that 99.66% of the variation in the GEI can be explained by the three independent variables. These findings imply that strengthening women’s economic roles and political participation is essential to improving gender empowerment in Aceh.